Labor informality effects of a poverty-alleviation program - Gasparini, Leonardo (2007)
In the midst of a serious macroeconomic crisis Argentina implemented a large social program -the Programa Jefes de Hogar (PJH)- that provides cash transfers to unemployed household heads meeting certain criteria. In practice, giving the difficulties in monitoring informal jobs, the unemployment requirement of the PJH would imply a disincentive for the program participants to search for a formal job. By applying matching techniques we evaluate the empirical relevance of this prediction during the period of strong economic growth that followed the crisis. We find some evidence on the informality bias of the PJH when the value of the transfer was relatively high compared to wages in the formal labor market.